2017
DOI: 10.1523/jneurosci.0610-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Impact of a Looming Stimulus onto the Body Is Subserved by Multisensory Integration Mechanisms

Abstract: In the jungle, survival is highly correlated with the ability to detect and distinguish between an approaching predator and a putative prey. From an ecological perspective, a predator rapidly approaching its prey is a stronger cue for flight than a slowly moving predator. In the present study, we use functional magnetic resonance imaging in the nonhuman primate, to investigate the neural bases of the prediction of an impact to the body by a looming stimulus, i.e., the neural bases of the interaction between a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 113 publications
4
54
0
Order By: Relevance
“…More precisely, the PPS constraint specifies that body signals occur within the limited space surrounding the body—the PPS—and hence for signals to bind with body‐related information they must occur within this space. In this line, recent work has depicted a more complete picture regarding the encoding and functional role of the PPS, and has revealed the stochastic and predictive nature of this particular form of spatial representation critical for bodily self‐consciousness. Thus, we propose that by highlighting the stochastic or statistical inference nature of PPS representation, as one fundamental component of bodily self‐consciousness, it may be possible to leverage recent advances in computational models dedicated to multisensory integration in the study of bodily self‐consciousness.…”
Section: Bodily Self‐consciousnessmentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely, the PPS constraint specifies that body signals occur within the limited space surrounding the body—the PPS—and hence for signals to bind with body‐related information they must occur within this space. In this line, recent work has depicted a more complete picture regarding the encoding and functional role of the PPS, and has revealed the stochastic and predictive nature of this particular form of spatial representation critical for bodily self‐consciousness. Thus, we propose that by highlighting the stochastic or statistical inference nature of PPS representation, as one fundamental component of bodily self‐consciousness, it may be possible to leverage recent advances in computational models dedicated to multisensory integration in the study of bodily self‐consciousness.…”
Section: Bodily Self‐consciousnessmentioning
confidence: 99%
“…One of the most notorious recent conceptual developments is the specific interplay between prediction and PPS . Indeed, a number of different groups utilizing vastly different techniques and populations have highlighted the strong role of PPS in inference.…”
Section: Bodily Self‐consciousnessmentioning
confidence: 99%
“…Here, we propose and demonstrate that it is possible to delineate and measure a representation of PPS within virtual and mixed reality (MR) environments. Several lines of work in neurophysiology and neuroimaging have shown that PPS representation is implemented by specific neuronal populations, which selectively integrate tactile stimuli on the body with visual or auditory cues related to external objects as they approach the body (Ladavas and Serino, 2008;Macaluso and Maravita, 2010;Cléry et al, 2015Cléry et al, , 2017. In this manner, the brain builds a representation of spatial locations in the environment where body-objects points of contact may potentially occur (Cléry et al, 2015(Cléry et al, , 2017, a mechanism which is postulated to be fundamental for defensive as well as for approaching behaviors (Cléry et al, 2015;de Vignemont and Iannetti, 2015).…”
mentioning
confidence: 99%
“…Several lines of work in neurophysiology and neuroimaging have shown that PPS representation is implemented by specific neuronal populations, which selectively integrate tactile stimuli on the body with visual or auditory cues related to external objects as they approach the body (Ladavas and Serino, 2008;Macaluso and Maravita, 2010;Cléry et al, 2015Cléry et al, , 2017. In this manner, the brain builds a representation of spatial locations in the environment where body-objects points of contact may potentially occur (Cléry et al, 2015(Cléry et al, , 2017, a mechanism which is postulated to be fundamental for defensive as well as for approaching behaviors (Cléry et al, 2015;de Vignemont and Iannetti, 2015). In monkey neurophysiology, PPS has been studied by measuring the response properties of multisensory neurons, mainly located in the ventral premotor cortex (Rizzolatti et al, 1981;Graziano et al, 1997) and the posterior parietal cortex (Duhamel et al, 1998;Avillac et al, 2005).…”
mentioning
confidence: 99%
“…electrophysiological recordings, calcium imaging, optogenetics). This whole brain mapping can be performed for a more detailed body representation and combined to other sensory modalities (visual, auditory) to explore multisensory integration process (Cléry et al, 2015(Cléry et al, , 2017b(Cléry et al, , 2020, or to functional tasks to explore motor-related function such as grasping (Tia et al, 2017). auditory anterolateral area; AuCl, auditory caudaolateral area; AuCPB, auditory caudal parabelt area; AuML, auditory middle lateral area; AuRT, auditory rostrotemporal area; AuR, auditory rostral area; FST, fundus of the superior temporal sulcus; IPa, intraparietal sulcus associated area;…”
Section: Perspectivesmentioning
confidence: 99%